Implementasi Model Pembelajaran Visuospatial (3D) untuk Mengembangkan Kemampuan Kognitif Calon Guru Biologi pada Konsep Anatomi Tumbuhan - Purwati Kuswarini Suprapto (Bioedusiana: Jurnal Pendidikan Biologi, 2016)
The study on the implementation of visuospatial teaching models (VS-Model) for the enhancement of cognitive ability of prospective teacher on plant anatomy concept has been done descriptively. VS model is a model of learning to involve the ability of three-dimensional (3D). The study aimed to determine the effectiveness of VS-Model on improving cognitive ability of prospective biology teacher on plant anatomy concept. Participants of the study were 108 fourth semester biology education students attending Plant Anatomy Course in academic year of 2011 of Siliwangi University of Tasikmalaya, West Java. All participants were divided into three different class. Each class implemented three different type of VS-Model, e.g. Inductive Playdoch (IP), Inductive Images (IG), and Deductive Images (DG). Measurement of cognitive abilities C1, C2 and C3 was done by a written test, 32 items, the ability of analize (C4) used the assessment of 2D images, the ability of evaluate (C5) was done by observation of students' ability to evaluate students during a presentation in class and ability of create (C6) measured from the assessment of 3D images and 3D play doh.The results showed that the VS- model can improve the cognitive abilities of students. VS model with Inductive -Picture (IG) can improve understand (C2), whereas Deductive-Picture (DG) was able to develop the ability apply (C3). All three treatments could not be analyzed (C4) microscopic observation well. However, the ability to remember (C1), evaluate (C5) and create (C6) of 3D was very well developed in Inductive-Play doh (IP).